Contamination of soils public places and children'splaygrounds by Toxocara canis and Toxocara cati eggs in Saladdin province - Abd A. Erdeni; Ashraf J. Mahmoud Zangana (Kirkuk Journal of Science, 2016)
To determine the prevalence of Toxocara canis and T. cati eggs in public places and children playgrounds, 783 soil samples were collected from 15 different regions in Saladdin provinces during July 2012 to June 2013 . Toxocara species eggs are found in 192 samples 24.52% . The Contamination with these eggs is observed in all sites like Tikrit &Baiji & Samaraa & Al-Dujail district , Al-Alam & Amerli &Al-Senia & Al-Ouja region ,the village of Albu-Ajil . The soils of Gardens have more contaminated than bare soils . Higher contamination rate noticed in February 55.71% and March 52.30% while it decreased to lower level in June 2013 14.75%